Inflammation and immunity gene expression profiling of macrophages on mineralized collagen. Issue 8 (4th November 2020) - Meng, Chunxiu; Liu, Kun; Lv, Zhaoyong; Zhang, Yujue; Li, Jun; Luo, Xin; Qiang, Huifen; Li, Keyi; Liu, Fengzhen; Zhang, Bin; Cui, Fuzhai
Abstract: Mineralized collagen (MC) is a biomaterial that is commonly used in the treatment of bone defects. However, the inflammatory response after biomaterial implantation is a recurrent problem that requires urgent attention. Our previous studies on MC‐macrophage interactions were descriptive but we did not perform an in‐depth analysis on a genetic level to investigate the underlying mechanisms. In this study, we cultured RAW264.7 cells on MC or collagen and examined the proliferation of the macrophages by Cell Counting Kit‐8 assay. We sequenced the RNA of the cultured cells to discover differential gene expression patterns and found that a total of 1183 genes were differentially expressed between the MC‐ and collagen‐cultured groups, of which 396 genes were upregulated and 787 were downregulated. Gene ontology analysis revealed that biological processes in MC‐cultured cells, such as inflammation and innate immunity, were downregulated; whereas nucleosome assembly, megakaryocyte differentiation, and chromatin assembly were upregulated. We identified several pathways associated with immunity that were significantly enriched using the Kyoto Encyclopedia of Genes and Genomes. Furthermore, we validated the differentially expressed genes from RNA sequencing by quantitative real‐time polymerase chain reaction. This study provides insight into the macrophage phenotype based on the microenvironment, which is the foundation for the clinical application of MC‐based interventions.